The effect of mild and moderate hepatic impairment on the pharmacokinetics of tofacitinib, an orally active Janus kinase inhibitor. Issue 6 (1st October 2014) - Lawendy, Nervin; Lamba, Manisha; Chan, Gary; Wang, Rong; Alvey, Christine W.; Krishnaswami, Sriram
Abstract Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis. We report here an evaluation of the pharmacokinetics of a single 10 mg dose of tofacitinib in healthy volunteers (n = 6) and subjects with mild (n = 6) or moderate (n = 6) hepatic impairment. Compared to healthy volunteers, tofacitinib area under the plasma concentration–time profile from time 0 to infinity (AUCinf) and maximum observed concentration (Cmax) in subjects with mild hepatic impairment were not altered. In subjects with moderate hepatic impairment, the geometric mean AUCinf and Cmax of tofacitinib were increased (90% confidence intervals of percentage increase) by approximately 65% (25%, 117%) and 49% (12%, 97%), respectively. A single dose of tofacitinib 10 mg resulted in two treatment‐emergent adverse events (AE) in the mild hepatic impairment group, and one in the moderate hepatic impairment group; they were not considered related to study treatment. There were no deaths, serious AEs, discontinuations due to AEs, or dose reductions due to AEs. Data from this study were critical to deriving dose adjustments for subjects with hepatic impairment.